Pesantren Sebagai Bentuk Identitas Pendidikan Islam - Mahrus (Jurnal Pendidikan Islam, 2018)
Abstract: Islamic boarding school is one of the dominant Islamic education institutions and emphasizes religious studies that influence and impact the culture, tradition and preservation of Islamic teachings. Islamic boarding schools also play a role in the formatio n of a nation's civilization. Pesantren at this time must be prepared to face the challenges of globalization and produce graduates who can compete and fill the global era. For this reason, pesantren must be able to become institutions that are global in m ind and have capable resources, especially in Islamic education. Therefore, it is necessary to change the mindset of pesantren into a mindset that follows change, which is oriented towards the creation of graduates who have three abilities, namely: (1) the ability to survive (survive) amidst continuous changes and competition, ( 2) the ability to improve the quality of life (spiritual and physical), (3) the ability to develop and adapt to the changing demands of the times